Broadband Circular Polarizer Based on Plasmon Hybridizations. (7th March 2017) - Shi, Hong-Yu; Li, Wei; Zhu, Shi-Tao; Dong, Xiao-Li; Zhang, An-Xue; Xia, Song; Xu, Zhuo
Abstract : This paper presents a broadband circular polarizer with a ring/disk cavity structure, which is a broadband application of plasmon hybridizations. The proposed design can convert a linearly polarized wave to a circularly polarized wave from 12.66 GHz to 17.43 GHz within a bandwidth of 30%. The broadband polarization conversion characterization results from the different plasmon hybridization modes induced in the ring/disk cavity. The proposed broadband circular polarizer is demonstrated by both full-wave simulation and measurement.